PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY AR PADA MATA PELAJARANDASAR – DASAR PROGRAM KEAHLIAN DDPK KELAS X DI SMK N 1 RAO SELATAN - Mulya, Beni; Mulyono, Heri; Alfiriani, Adlia (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The problems that exist in the basic lessons of the DKV (Visual Communication Design) skills program are the lack of knowledge of the use of technology in developing innovative and creative learning media, and not yet using augmented reality-based learning media in the teaching and learning process and the difficulties experienced by students in understanding the material provided about typographic composition. This research aims to develop augmented reality-based learning media with valid and practical qualifications. Researchers use Research and Development (RnD) research using the ADDIE model. The data collection technique in this research used a questionnaire. The research results showed that the average validity test value for media experts was 84.65% in the very valid category and material experts were 95.83% in the very valid category. The practicality test obtained a student questionnaire response percentage score of 90.20% in the very practical category and a teacher response questionnaire percentage score of 95.31% in the very practical category. It can be concluded that Augmented Reality-based learning media in the basic subjects of the Visual Communication Design (DKV) skills program at SMK N 1 Rao Selatan is suitable for use.